Analisis Faktor Penerapan Lean Construction dalam Manajemen Material Menggunakan Metode Relative Importance Index (RII) - Assidiqi, Widinanta Emir; Beatrix, Michella (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify and analyze the most critical factors in the implementation of Lean Construction within construction project material management through a quantitative approach and the Relative Importance Index (RII) method. The research variables encompass aspects of planning, procurement, storage, distribution, and material control to determine the priority ranking of the influencing factors. The analysis results indicate that poor contractor site management is the most dominant factor with the highest Relative Importance Index value, followed by constraints in shop drawings, construction method errors, and weak communication between parties. Overall, these findings confirm that managerial aspects and field coordination play a highly significant role in the successful implementation of Lean Construction to minimize material waste in construction projects.